RURAL AREAS IN THE SOCIO-ECONOMIC SYSTEM OF EU COUNTRIES (Polityki Europejskie, Finanse i Marketing)
The study undertakes the problem of identifying, cataloguing, and evaluating rural areas and intermediate areas of European Union countries, for four selected variables which describe: area, share of population, share of employed, and share of gross value added (GVA). Tabular analyses and cluster analysis ware conducted, and the statistical information was differentiated through classification trees. The research revealed multidimensional diversification of rural areas and their meaningful, although diverse, relevance within the economic systems of individual countries. 34,7% of the EU population reside in strictly rural areas, which make up 49,7% of the EU geographic area. The share of employed in rural areas in the EU amounts to 26,7%. Additionally, the contribution of the rural areas to elaborated gross value added adds up to 13%. The taxonomy resulted in the extraction of three groups (clusters), each containing eight countries. According to that comprehensive evaluation of rural areas, Poland is similar to the Czech Republic, Denmark, France, Latvia and Germany.